The six-year decomposition of coarse woody debris drives shifts in soil fungal communities in subtropical forests - Wang, Nan; Ding, Binle; Zhang, Ruyi; Chen, Hui; Xie, Tingsi; Bai, Shangbin; Chen, Hua; Pan, Xiaocheng (Frontiers in Microbiology, 2025)
IntroductionCoarse woody debris (CWD) plays a vital role in forest ecosystems, serving as a reservoir for carbon sequestration. While global climate change is expected to exacerbate forest disturbances and lead to a significant accumulation of CWD, the effect of CWD decomposition on the composition, diversity and functional traits of soil fungal communities remains unclear, especially for subtropical forests with high tree species diversity.MethodsHere, we conducted a 6-year in situ field experiment (2018–2024) in a subtropical evergreen broad-leaved forest in southern China. We used high-throughput sequencing and qPCR to examine how decomposition of three dominant tree species (conifer, broadleaved, and woody monocot moso bamboo) influences soil fungal composition, and applied the FUNGuild tool to infer fungal trophic modes and functional groups from sequencing data. We found that 6 years of CWD decomposition significantly increased soil organic carbon (SOC), dissolved organic carbon (DOC), and microbial biomass carbon (MBC) while reducing soil pH. Bamboo CWD showed the highest SOC and MBC accumulation.ResultsHigh-throughput sequencing of the ITS1 region indicated a statistically significant increase in α-diversity and a marked differentiation in β-diversity of fungal communities following decomposition. Taxonomic analysis identified Ascomycota and Basidiomycota as the dominant fungal phyla. CWD decomposition was associated with observable differences in taxonomic composition, specifically an increase in the Basidiomycota-to-Ascomycota ratio. Key gener as such as Geminibasidium, Trichoderma, and Trechispora exhibited species-specific responses to both CWD decomposition and tree species identity. Functional analysis via FUNGuild revealed an increased relative abundance of taxa predicted to be saprotrophic, alongside a decreased relative abundance of taxa inferred to be symbiotrophic. Soil pH and SOC emerged as the primary factors influencing fungal community structure.DiscussionThese findings highlight the critical role of CWD in shaping soil fungal communities and their inferred functional traits, underscore the influence of tree species identity on fungal assembly, and provide insights into stable carbon sequestration stability in subtropical forests.